The The Role of Self-Esteem in Predicting Family Independence in Long-Term Elderly Care - Budiarti, Nadin; Melizza, Nur; Adiratna, Brillian Yunita; Yossi, Suyesti; Surya, Berlyan; Hermanto, Roby Putra (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2025)
As the number of elderly people in Indonesia increases, so does the need for long-term care. In this case, the family acts as the main caregiver who not only provides physical, but also emotional and social support. Family independence is key to successful care, while family members' self-esteem is believed to influence their readiness to carry out this role. The purpose of this study was to determine the relationship between the level of self-esteem of family members and family independence in caring for the elderly. This quantitative study with a cross-sectional design involved 59 respondents in Malang City who were actively involved in caring for the elderly at home who were selected by accidental sampling. Data were collected through the Rosenberg Self-Esteem Scale (RSES) and family independence questionnaire, then analyzed with the Spearman Rank test. The majority of respondents demonstrated high self-esteem (35.6%) and high family independence (KM 4). However, the Spearman Rank test revealed no significant correlation between self-esteem and family independence (p = 0.342; r = -0.126). Other factors such as age, family structure, occupation, and cultural values are thought to be more influential. Self-esteem contributes psychologically, but improving family self-reliance requires a comprehensive approach that includes social, economic, and cultural aspects. Psychosocial and culture-based approaches are important in building an independent, sustainable, and empathetic elder care system.